“Good-bye, Khmer Rouge!”: Oral Memory and Borderer Life in Globalization of Khmer Diaspora - Monnaramit, Supawadee (Journal of Mekong Societies, 2013)
This article is aimed at demonstrating the everyday life of the Khmer Diaspora in Thailand. To avoid the Khmer Rouge regime, the Khmer Diaspora fled across the Thai-Khmer border to Klong Yai district, Trat province in Thailand. They tried to adopt Thai spiritual beliefs and traditions in order to assimilate into Thai society. At the same time, they also maintained their relationships across the border and their Khmer traditional culture.